2012
DOI: 10.1016/j.immuni.2012.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-15-Dependent NKp46+ Innate Lymphoid Cells Control Intestinal Inflammation by Recruiting Inflammatory Monocytes

Abstract: With the goal in mind to define how interleukin-15 (IL-15) contributes to acute intestinal inflammation, we have used a mouse model of ileitis induced by oral infection with Toxoplasma gondii. We observed that a crosstalk between IL-15 and interleukin-18 (IL-18) promoted intestinal recruitment of inflammatory monocytes, where these cells participated in parasite control but also in tissue damage. A stromal source of IL-15 controlled the development of lamina propria NKp46 + NK1.1 + cells, whereas IL-18 produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 53 publications
(68 reference statements)
4
82
1
3
Order By: Relevance
“…Synergistic expression of ROP16 and GRA15 increases parasite susceptibility within IFN-␥-and TNF-␣-stimulated macrophages. Inflammatory macrophages that are recruited to the intestine are critically important for the host to limit Toxoplasma replication and promote host resistance at the site of infection (32,33). Since ROP16 and GRA15 had a drastic effect on parasite burden in vivo, we tested whether the type II engineered strains differed in their ability to evade macrophage toxoplasmacidal mechanisms elicited by stimulation with IFN-␥ and TNF-␣, cytokines that are expressed in the intestine following oral infection (20).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Synergistic expression of ROP16 and GRA15 increases parasite susceptibility within IFN-␥-and TNF-␣-stimulated macrophages. Inflammatory macrophages that are recruited to the intestine are critically important for the host to limit Toxoplasma replication and promote host resistance at the site of infection (32,33). Since ROP16 and GRA15 had a drastic effect on parasite burden in vivo, we tested whether the type II engineered strains differed in their ability to evade macrophage toxoplasmacidal mechanisms elicited by stimulation with IFN-␥ and TNF-␣, cytokines that are expressed in the intestine following oral infection (20).…”
Section: Figmentioning
confidence: 99%
“…TFBS enrichment analysis (DiRE) was performed on all Peyer's patch genes that were upregulated, on average, 1.7-fold following infection compared to the level of regulation in the uninfected sample [0.8 Ͻ log 2 (average gene expression of type II and estingly, Ccl1 and Ccl3 chemokine gene expression was highly induced by the IIϩROP16 I strain, while coagulation factors (F5 and F13a1) were downregulated. CCL3 and its receptor, CCR1, were recently shown to be required for inflammatory monocyte recruitment to the intestine of Toxoplasma-infected mice, which in turn limited the intestinal parasite burden (32). Considering that a putative STAT5 TFBS sequence is 500 bp upstream of the transcriptional start site of CCL3 (not shown), it remains to be determined whether gene expression of Ccl3 by the IIϩROP16 I strain requires host STAT5 and/or NF-B.…”
Section: Figmentioning
confidence: 99%
“…We have recently shown that, in the acute stage of infection, DCs secrete high levels of IL-12, triggering adaptive immunity (9). The proinflammatory cytokine IFN-g produced mainly by activated innate lymphoid cells, NK, and T cells is the major driving factor for host protection against this intracellular pathogen (10,11). In our previous studies, we detected that Ly6C high Gr1 + monocytes were crucial during the acute stage of T. gondii infection, producing high amounts of TNF, inducible NO synthase (iNOS), and reactive oxygen intermediates (ROS), which directly contributed to the control of the parasite burden in the host (6,7,12,13).…”
mentioning
confidence: 99%
“…Dans l'intestin, les ILC1 sont la source innée prédominante d'IFN- en réponse à l'IL-12 ou, par exemple, à une infection intestinale par le parasite Toxoplasma gondii [25]. Elles participent en effet, avec les lymphocytes T qui produisent de l'IFN-, au contrôle de la réplication du parasite et assurent le recrutement des monocytes inflammatoires [25,34]. Les souris Rag1 -/-Tbet -/-comme les souris Rag1 -/-Ifng -/-sont aussi plus sensibles à l'infection par Clostridium difficile que les souris uniquement invalidées pour le gène Rag1.…”
Section: Les Ilc1unclassified